ON THE ISSUE OF THE REASONABLE SEPARATION AND COMPOSITION UNITY OF GREGORY’S IV–V ORATIONS AGAINST EMPEROR JULIAN - A. USACHEVA (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2011)
The article is devoted to the research of the composition of St. Gregory’s speeches against Emperor Julian (Or. IV–V). The article proposes the hypothesis of the composition’s unity of the IV & V speeches and suggests the explanation of their formal division. The hypothesis is argued by the analysis of the relationship between contemporary works of Libanius, Julian and St. Gregory. In our view, the compositional unity of the text was reached by the author’s fi nal edition: St. Gregory matched the material and the basic ideas of two speeches primarily by means of the introduction of the IV speech and conclusion of the V speech, which had been written in the same semantic and stylistic attitude as a single frame of the speec